LIFE CYCLE ASSESSMENT OF PORTLAND COMPOSITE CEMENT (CASE STUDY: PT X) - DEVIA NIM: 25315010, DELLA
Cement industry facing the challenge in reducing resource material consumption and energy through sustainable development. PT X is one of the cement industry in Indonesia which produced portland composite cement which is considered more environmentally friendly because it contains less clinker than ordinary portland cement. Purpose of this study is to identify the product life cycle stages that have a significant impact and define alternative improvement scenarios which have the least potential impact on the life cycle of portland composite cement. The method used is Life Cycle Assessment (LCA) which consists of (1) goal and scope definition, (2) inventory analysis, (3) impact assessment, and (4) interpretation. Scope of LCA is cradle-to-gate from material extraction, production process and cement distribution. The potential impact from portland cement composite are global warming potential (GWP) about 768.43 kgCO2eq, acidification potential (AP) about 0,75 kgSO2eq, particulate matter formation potential (PMFP) about 0.26 kgPM2,5eq, photochemical ozone formation potential (POFP) about 2,31 kg NOxeq and human toxicity with cancer (HTPc) about 5,11E-03 kg 1,4DCBeq. The biggest potential impact is GWP which has the greatest normalization value among others, about 1.51E-11 in total. The largest contribution is in the production process stage about 88.84%, which caused by CO2 emissions about 98.63%. The recommended scenario for reducing the potential impact of GWP is carbon capture technology with a reduction of 57%.